PHYSICAL EDUCATION PERSPECTIVES IN MERDEKA BELAJAR PROGRAM IN INDONESIA - Dedi Aryadi; Forbis Ahamed (Prosiding Amal Insani Foundation, 2026)
The Merdeka Belajar—Kampus Merdeka (MBKM) policy provides flexible learning opportunities in higher education through learning experiences outside of study programs, including field practice and interdisciplinary collaboration. In this context, physical education plays a strategic role not only in developing physical fitness but also in character building, sportsmanship, leadership, and teamwork relevant to 21st-century learning outcomes. This study aims to describe the perspective of physical education in the implementation of the MBKM program in Indonesia. The study used a qualitative descriptive approach with data collection techniques through literature studies, policy document analysis, and research findings related to the implementation of MBKM in the field of physical education. Data analysis was carried out through data reduction, data presentation, and thematic conclusion drawing. The study results indicate that physical education within the MBKM framework contributes to strengthening students' pedagogical, professional, and social competencies through activities such as the Teaching Campus (Kampus Mengajar), teaching assistantships, and humanitarian projects based on physical activity and health. Furthermore, the experiential learning approach encourages students to integrate health literacy, character education, and sports learning innovations contextually. However, program implementation still faces challenges such as limited infrastructure, curriculum synchronization, and institutional understanding of the flexibility of the MBKM scheme. This study concludes that physical education has a strategic position in supporting the transformation of experiential learning in the MBKM era, thus requiring strengthening institutional policies and adaptive and sustainable implementation models.